The Effectiveness of Minang Mart Partnership Pattern in Empowering Local Micro, Small, and Medium Enterprises in West Sumatra - Rendi Febria Putra; Kismartini Kismartini; Retno Sunu Astuti (Universitas Medan Area, 2022)
This article aims to discuss the effectiveness of the Minang Mart partnership pattern in empowering local Micro, Small, and Medium Enterprises in Padang City, West Sumatra. The problem is focused on the realization of Minang Mart's idea for empowerment and collaboration with local traders and MSMEs. Along with its development, Minang Mart has come out of the initial idea, namely the modernization and empowerment of local traders, and local Micro, Small, and Medium Enterprises have not been implemented until now. To approach this problem, Nugroho's theoretical reference was used regarding the effectiveness of a policy which was put forward in four